Sr isotope composition of Golden Delicious apples in Northern Italy reflects the soil 87Sr/86Sr ratio of the cultivation area. (25th April 2020) - Aguzzoni, Agnese; Bassi, Michele; Pignotti, Emanuela; Robatscher, Peter; Scandellari, Francesca; Tirler, Werner; Tagliavini, Massimo
Abstract: BACKGROUND: Apples have a leading role in the Italian fruit sector, and high‐quality apples, including the Golden Delicious variety, are cultivated mainly in the Northern mountain districts. In the present study, Golden Delicious apples from PDO (Protected Designation of Origin) and PGI (Protected Geographical Indication) cultivation districts were characterized according to their Sr isotope composition and compared with apples from other Northern Italian districts. RESULTS: Apples collected in two consecutive years (2017 and 2018) confirmed the low annual variability of the 87 Sr/ 86 Sr ratio. The isotope ratio of apples was highly correlated with that of the soil extracts of the respective orchards. Statistical differences were highlighted between cultivation districts. However, because similar geological features characterized some areas, their ratios overlapped and a complete separation of the districts was not possible. CONCLUSION: The 87 Sr/ 86 Sr ratio is an excellent marker for studies of food traceability because it retains the information about the place of origin. However, its strength is limited when comparing products from cultivation areas sharing similar geological features. In the perspective of geographical traceability, a multichemical characterization can overcome the limits of single‐parameter approach. © 2020 The Authors. Journal of The Science of Food and Agriculture published by John Wiley & Sons Ltd on behalf of Society of Chemical Industry.